2022
DOI: 10.3390/catal12070756
|View full text |Cite
|
Sign up to set email alerts
|

Phyco-Synthesized Zinc Oxide Nanoparticles Using Marine Macroalgae, Ulva fasciata Delile, Characterization, Antibacterial Activity, Photocatalysis, and Tanning Wastewater Treatment

Abstract: The aqueous extract of marine green macroalgae, Ulva fasciata Delile, was harnessed for the synthesis of zinc oxide nanoparticles (ZnO-NPs). The conversion to ZnO-NPs was characterized by color change, UV–vis spectroscopy, FT-IR, TEM, SEM-EDX, and XRD. Data showed the formation of spherical and crystalline ZnO-NPs with a size range of 3–33 nm. SEM-EDX revealed the presence of Zn and O in weight percentages of 45.3 and 31.62%, respectively. The phyco-synthesized ZnO-NPs exhibited an effective antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 88 publications
(133 reference statements)
0
17
0
Order By: Relevance
“…The “greening” of this process led to the cessation of the use of large quantities of harmful organic substances, an increase in efficiency, a reduction in toxicity and eco-toxicity, and a reduction in the process price in comparison to previous physical and chemical methodologies [ 2 , 6 ]. Great success in the synthesis of metal and metal oxide nanoparticles that exhibited different biological and catalytic activities, such as silver, ZnO and MgO nanoparticles, was achieved using plant extracts, marine macroalgae ( Ulva fasciata Delile), bacteria Pseudomonas aeruginosa , and brown algae ( Cystoseira crinita ) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The “greening” of this process led to the cessation of the use of large quantities of harmful organic substances, an increase in efficiency, a reduction in toxicity and eco-toxicity, and a reduction in the process price in comparison to previous physical and chemical methodologies [ 2 , 6 ]. Great success in the synthesis of metal and metal oxide nanoparticles that exhibited different biological and catalytic activities, such as silver, ZnO and MgO nanoparticles, was achieved using plant extracts, marine macroalgae ( Ulva fasciata Delile), bacteria Pseudomonas aeruginosa , and brown algae ( Cystoseira crinita ) [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy confirmed the presence of gold nanoparticles produced intracellularly by Cholera vulgaris, as described by Luangpipat et al (16) . The Size, aggregation, shape, surface charge, and stability are only few of the factors that affect a nanoparticle's activity (17) . Therefore, it is essential to determine the morphological characteristics, especially the size, shape, and aggregation of the synthesized nanocomposite.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the review emphasizes the potential applications of green-synthesized ZnO-NPs in various fields, including wastewater treatment [ 31 ]. The study by Fouda et al [ 32 ] explored the potential of using Ulva fasciata in the green synthesis of ZnO-NPs. The results indicated that the algae extract could successfully reduce zinc ions to ZnO-NPs in a fast and eco-friendly manner.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ZnO-NPs were found to exhibit good photocatalytic activity towards the degradation of methylene blue, and they were also able to remove Cr(VI) ions from tanning wastewater. The study concluded that Ulva fasciata Delile extract could be a promising and sustainable source for the green synthesis of ZnO-NPs with potential applications in various fields, including antibacterial and photocatalytic activities and tanning-wastewater treatment [ 32 ].…”
Section: Introductionmentioning
confidence: 99%